Women, Careers, and Trust: Reflections on the Role of Women in Islam in the Contemporary Era - Anisa Fitriyani; Endad Musaddad (Aslama: Journal of Islamic Studies, 2025)
This study discusses the role of women in the field of careers from the perspective of Islam and gender equality in the contemporary era. Social changes and increased access to education have encouraged women to be more actively involved in the public sphere, including the professional workforce. In Islam, women are given the opportunity to pursue careers as long as they adhere to the principles of Sharia and maintain a balance in their familial roles. A career is understood as a trust (amanah) that demands professionalism, responsibility, and honesty from both men and women. However, women often face dual challenges, having to fulfill their roles as wives, mothers, and workers simultaneously. Therefore, role-sharing and cooperation between husband and wife are essential in achieving justice within the family. This study also explores how the status of women has changed significantly before and after the advent of Islam from being marginalized to being more appreciated in various aspects of life. In the context of gender equality, Islam emphasizes the principle of justice rather than mere role similarity, allowing women to be empowered without sacrificing their natural disposition (fitrah). Using a qualitative approach with descriptive analysis, this study shows that Islam supports women's participation in the workforce in a proportional, just, and dignified manner.